OPTIMALISASI POTENSI DESA SINDANGSARI MELALUI INOVASI PEMBUATAN ES KRIM JAHE MERAH - Afif Nurseha; Ajat Saputra; Rika Kurniati; Sri Wahyuni; Tia Faujiah (Yayasan Education and Social Center, 2022)
Sindangsari Village is a village located in Kasomalang District, Subang Regency, which has the potential of toga plants, especially red ginger. The results of red ginger cultivation are processed into traditional red ginger drinks. Processed in the form of traditional drinks are sold by the community but are limited because not all people like it. The purpose of this service is to educate the public through training on making red ginger processed innovations, namely red ginger ice cream. The research method used is through indirect training by recording every step that is practiced from making red ginger ice cream. The recording is then uploaded to a YouTube account. The results achieved from this service activity are the creation of red ginger processed innovations in the form of red ginger ice cream